ORGANIZATIONAL CHANGE, CULTURE, AND EMPLOYEE PERFORMANCE: MEDIATING ROLE OF JOB SATISFACTION AT KSOP CLASS III TANJUNG PAKIS - Suyanti Suyanti; Sri Rahayu; Anita Kartika Sari (STMIK Indonesia Banda Aceh, 2026)
Public sector maritime agencies are undergoing comprehensive transformations encompassing organizational restructuring and digital service implementation, yet the mechanisms through which such changes influence employee performance remain inadequately understood. This study examines the effects of organizational change and organizational culture on employee performance, with job satisfaction posited as a mediating variable, within a specific Indonesian port authority context. Employing a quantitative explanatory research design, data were collected from active employees through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling. The measurement instrument demonstrated robust psychometric properties with satisfactory validity and reliability indices. Results indicate that organizational change exerts a significant positive effect on job satisfaction, while organizational culture demonstrates a significant direct positive effect on employee performance. However, organizational culture does not significantly influence job satisfaction, and job satisfaction fails to significantly affect employee performance. Crucially, job satisfaction does not mediate the relationships between either organizational change or organizational culture and employee performance, indicating that direct mechanisms predominate over indirect psychological pathways in this public sector context. These findings challenge the universal applicability of established mediation models and suggest that institutional constraints and normative compliance mechanisms may supersede individual affective states as performance drivers in highly regulated bureaucratic settings. The study contributes to organizational behavior literature by identifying boundary conditions for mediation theories and offers practical implications for maritime public service managers prioritizing culture-based performance management and sustained capacity-building alongside structural reforms.